Remission Induced by TNF Inhibitors Plus Methotrexate is Associated With Changes in Peripheral Naïve B Cells in Patients With Rheumatoid Arthritis - Hernández-Breijo, Borja; Plasencia-Rodríguez, Chamaida; Navarro-Compán, Victoria; García-Hoz, Carlota; Nieto-Gañán, Israel; Sobrino, Cristina; Bachiller-Corral, Javier; Díaz-Almirón, Mariana; Martínez-Feito, Ana; Jurado, Teresa; Lapuente-Suanzes, Paloma; Bonilla, Gema; et al. (Frontiers in Medicine, 2021)
Biological therapies, such as TNF inhibitors (TNFi), are increasing remission (REM) rates in rheumatoid arthritis (RA) patients, although these are still limited. The aim of our study was to analyze changes in the profile of peripheral blood mononuclear cells (PBMC) in patients with RA treated with TNFi in relation to the clinical response. This is a prospective and observational study including 78 RA patients starting the first TNFi. PBMC were analyzed by flow cytometry both at baseline and at 6 months. Disease activity at the same time points was assessed by DAS28, establishing DAS28 ≤ 2.6 as the criteria for REM. Logistic regression models were employed to analyze the association between the changes in PBMC and REM. After 6 months of TNFi treatment, 37% patients achieved REM by DAS28. Patients who achieved REM showed a reduction in the percentage of naive B cells, but only when patients had received concomitant methotrexate (MTX) (OR: 0.59; 95% CI: 0.39–0.91). However, no association was found for patients who did not receive concomitant MTX (OR: 0.85; 95% CI: 0.63–1.16). In conclusion, PBMC, mainly the B-cell subsets, are modified in RA patients with TNFi who achieve clinical REM. A significant decrease in naive B-cell percentage is associated with achieving REM after 6 months of TNFi treatment in patients who received concomitant therapy with MTX.